Strengthening capacities for community-based livestock health service delivery in the Ghibe Valley, Ethiopia - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The purpose of this project is to strengthen local capacity for innovation in animal health systems in Ghibe Valley, Ethiopia. The project employs action research using asset-based community development (ABCD) and innovation systems (IS) approaches to derive lessons on (1) how to bring about sustainable improvements in livestock health service delivery in the project site and (2) how to translate improved livestock health into increased productivity and incomes.